The Impact of Time Spent on Social Media on the Occurrence of Anxiety in Youth: A Cross-Sectional Study in Surakarta, Indonesia - Aris Widiyanto; Joel Rey Ugsang Acob; France Allan M. Cavite; Tri Yuniarti; Joko Tri Atmojo (Journal Of Nursing Practice, 2025)
Background: In the era of technology and globalization, social media with youth is something that cannot be separated. However, the surge of information shared easily and sometimes unverified through social media can triggers anxiety, especially among teenager who spent overwhelmingly hours with social media.   Purpose: This study aimed to investigate the impact of time spent on social media on the occurrence of anxiety in youth. Methods: This cross-sectional study at the School of Health in Surakarta, Indonesia, examined into the association between social media usage and the levels of anxiety in college students. The method of simple random sampling from 300 student population was used to select the 213 students who comprised the samples. We used a questionnaire to gathering data from respondents then analyzed it using linear regression analysis for determining the correlation between variables. Results: The results of analysis showed that spending more than two hours a day on social media has a statistically significant effect on anxiety levels (β = 1.75; 95% CI = -0.31-3.19; p = 0.017). Conclusion: These results offer valuable insights for encouraging students to be aware of how their use of social media may affect their mental well-being. Implementing strategies such as establishing time limits on social media, incorporating breaks, and participating in activities that foster mental health, like exercise, hobbies, or offline social interactions, can prove advantageous.